2015
DOI: 10.1073/pnas.1512994112
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic membrane protein topological switching upon changes in phospholipid environment

Abstract: A fundamental objective in membrane biology is to understand and predict how a protein sequence folds and orients in a lipid bilayer. Establishing the principles governing membrane protein folding is central to understanding the molecular basis for membrane proteins that display multiple topologies, the intrinsic dynamic organization of membrane proteins, and membrane protein conformational disorders resulting in disease. We previously established that lactose permease of Escherichia coli displays a mixture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 34 publications
(46 reference statements)
3
80
0
Order By: Relevance
“…Is topological dynamics only possible as long as the protein interacts with the membrane-insertion machinery? Or is dynamics possible only when starting from high-energy, topologically frustrated states where, e.g., one or more TMH is not properly inserted into the membrane, or the membrane composition changes such that a preexisting topology becomes destabilized (33,34)?…”
Section: Discussionmentioning
confidence: 99%
“…Is topological dynamics only possible as long as the protein interacts with the membrane-insertion machinery? Or is dynamics possible only when starting from high-energy, topologically frustrated states where, e.g., one or more TMH is not properly inserted into the membrane, or the membrane composition changes such that a preexisting topology becomes destabilized (33,34)?…”
Section: Discussionmentioning
confidence: 99%
“…A precedent for lipid-induced inversion of transmembrane helices is found in the work of Dowhan and co-workers (15)(16)(17) with the lactose permease (LacY) of Escherichia coli. In elegant studies with LacY reconstituted into proteoliposomes, they demonstrated that addition of phosphatidyl ethanolamine to the proteoliposomes causes a previously periplasmic segment of LacY to become transmembrane, a change that alters the orientation of nearby transmembrane helices.…”
Section: Cholesterol-induced Changes In Loops 4 and 6 Of Scapmentioning
confidence: 99%
“…Heidi Vitrac, who joined our research group recently, reconstituted the dynamic properties of membrane proteins in a totally in vitro system composed of only LacY and lipids. She established that the rate of topological re-arrangement occurs on a time scale of seconds, making such changes of biological significance for any protein in any membrane potentially independent of other cellular factors (60). She also demonstrated that phosphorylation of a membrane protein extramembrane domain, which alters the charge balance between the protein and the membrane surface, results in a similar rapid change in topological organization (61).…”
Section: Membrane Protein Gymnastics In the Lipid Bilayermentioning
confidence: 99%